Outcome of metformin treatment in polycystic ovary syndrome - Anwary, SA; Alfazzaman, M; Bari, N; Islam, MR (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):60-65 The abstract of this article is available on the PubMed website